Effects of Aromatherapy With Citrus Aurantium Lavender on Sexual Function of Postmenopausal Women: A Randomized Controlled Trial - Zahra Abbaspoor; Foruzan Sharifipour; Amir Siahposh; Roghayeh Nazaralivand; Zeynab Mohaghegh; Shahla Faal Siahkal (Journal of Family and Reproductive Health, 2022)
Objective: The purpose of this study was to explore the effectiveness of aromatherapy with Citrus aurantium Lavender on the sexual function of postmenopausal women. Materials and methods: A randomized controlled trial with single-blind design was conducted on eighty postmenopausal women in Ahvaz, Iran from January to December 2019. The women were randomly assigned to the Citrus aurantium group (n=40) and placebo group (n=40). The intervention group received two drops of Citrus aurantium essential oil twice a day, for four consecutive days a week, for four weeks as inhalation. Similarly, placebo was received by the control group. Results: The results of this study revealed that in the intervention group, the FSFI total score and all of its dimensions were significantly improved compared to the control group. Conclusion: Aromatherapy using Citrus aurantium can be used as an alternative or complementary method for improvement of sexual function in postmenopausal women. It is recommended that the postmenopausal women suffering from sexual dysfunction be informed on the aromatherapy by Citrus aurantium essential oil.